1948
DOI: 10.1001/jama.1948.02900140001001
|View full text |Cite
|
Sign up to set email alerts
|

Embolism and Thrombosis in Coronary Heart Disease

Abstract: The problem of embolism and peripheral venous thrombosis has always been a major one in the treatment of heart disease and particularly of coronary heart disease. This is due to the prevalence of mural thrombi in the chambers of the heart, which may serve as a source of emboli, and to the occurrence of peripheral venous thrombi, especially in the legs. Several articles on the subject have appeared in the literature of the last few years, a splendid summary of which is given by Hellerstein and Martin,1 who also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1951
1951
1990
1990

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(4 citation statements)
references
References 7 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…73 In contrast, coronary artery thrombosis has been shown to occur infrequently in patients with subendocardial infarction (Table 3) in which the mechanism of infarction is believed to be due to reduced regional myocardial perfusion plus severe coronary artery stenosis, rather than acute thrombotic occlusion of the epicardial artery. 168 Barnes and Ball 9 Friedberg and Horn 92 Blumgart et al 21 Foord 90 Yater et al 347 Miller et al 191 Snow et al 289 Branwood and Montgomery 36 Spain and Bradess 292 Mitchell and Schwartz 195 Ehrlich and Shinohara 81 Meadows 188 Sinapius 282 Baroldi 11 Harland and Holburn 121 Jcfrgensen et al 149 Kagan et al 153 Spain and Bradess 293 Bouch…”
Section: Myocardial Infarctionmentioning
confidence: 99%
See 1 more Smart Citation
“…73 In contrast, coronary artery thrombosis has been shown to occur infrequently in patients with subendocardial infarction (Table 3) in which the mechanism of infarction is believed to be due to reduced regional myocardial perfusion plus severe coronary artery stenosis, rather than acute thrombotic occlusion of the epicardial artery. 168 Barnes and Ball 9 Friedberg and Horn 92 Blumgart et al 21 Foord 90 Yater et al 347 Miller et al 191 Snow et al 289 Branwood and Montgomery 36 Spain and Bradess 292 Mitchell and Schwartz 195 Ehrlich and Shinohara 81 Meadows 188 Sinapius 282 Baroldi 11 Harland and Holburn 121 Jcfrgensen et al 149 Kagan et al 153 Spain and Bradess 293 Bouch…”
Section: Myocardial Infarctionmentioning
confidence: 99%
“…Many patients with myocardial infarction will develop left ventricular mural thrombosis, 68,90,174,326 which may serve as a potential source of coronary artery embolization.…”
Section: Table 2 Incidence Of Coronary Thrombi In Patients With Tranmentioning
confidence: 99%
“…In this regard, a preliminary echocardiographic study of patients less than 5 weeks after infarction showed thrombus reduction or resolution in four of 10 patients treated with sulfinpyrazone (400 mg twice a day). 2 We chose sulfinpyrazone as the primary study drug since it appeared to inhibit platelet deposition in a similar model of arterial thrombosis in two of four patients with thrombi in abdominal aortic aneurysms. 25 Additionally, in randomized studies, sulfinpyrazone reduced the incidence of arteriovenous shunt thromboSiS33 and decreased the incidence of systemic embolism in patients with mitral stenosis, presumably by decreasing left atrial thrombus formation.34 In contrast.…”
Section: Resultsmentioning
confidence: 99%
“…What, then, is the role of coronary thrombosis in the pathogenesis of myocardial infarction? The frequency of coronary thrombosis in patients who die of myocardial infarction varies markedly in the published autopsy materials: 45 per cent ( I l ) , 53 per cent (3), 63 per cent (12), 69 per cent (8,23), 87 per cent (7), 92 per cent (18). The frequency of coronary thrombosis in all cases of death from coronary disease, both with and without myocardial infarction, is usually lower: 43 per cent (19),47percent (14),51 per cent (23), 52 per cent (5).…”
Section: Discussionmentioning
confidence: 99%